Fault isolation for nonisolated blocks. - Pomeranz, I. (IEEE Transactions on VLSI systems)
We consider circuits represented as interconnections of logic blocks. In such circuits, the goal of fault isolation is to identify which one of the blocks is faulty based on a faulty output response produced by the circuit. We study this issue and demonstrate that perfect or close-to-perfect fault isolation is possible with tests that propagate fault effects through pairs of blocks. We relate this phenomenon to the numbers of fault effects observed on the circuit outputs for faults in different blocks. For cases where fault isolation is not perfect, we insert observation points to ensure perfect fault isolation. We also study the number of tests required to achieve perfect fault isolation. The study is performed for single stuck-at faults in combinational (or full scan) blocks.